Task Effects on EFL Learners’ Production of Suggestions: A Focus on Elicited Phone Messages and Emails - Alicia Martínez-Flor (Miscelánea: A Journal of English and American Studies, 2006)
Scholars in the field of interlanguage pragmatics have examined second language learners’ development of pragmatics by means of employing different data collection instruments. Findings from this research have showed the existence of task effects, although the need to further investigate this area has been claimed by widening the types of instruments being employed as well as the context in which they are used. Accordingly, the present study aims at examining the task effects of two production instruments (phone messages and email tasks) on the learners’ use of suggestions in a foreign language setting. The participants included 81 Spanish university learners who were required to make suggestions in the oral and written production tasks. These tasks were elaborated on purpose for this study, and all situations i) varied according to the sociopragmatic factor of status; ii) were set at the University setting, as a familiar context to the participants; and iii) asked learners to perform suggestions in the role of students. Learners’ performance when making suggestions in the phone messages and email tasks was compared. The results revealed statistically significant differences, which support the fact that the production task in which learners are engaged in influences their use of suggestions. Moreover, the findings also showed that participants employed a higher number of appropriate suggestions in the written task than in the oral task. These findings are discussed and pedagogical implications highlighted.